WASATIAH DALAM MODERASI BERAGAMA MENURUT PENAFSIRAN AHMAD MUSTAFA AL-MARAGHI PADA SURAT AL-BAQARAH AYAT 142-143 - Al Habsyi, Muhammad Ali; Saladin , Bustami (UIN Mataram, 2024)
This article discusses the understanding of wasatiah in the interpretation of Ahmad Mustafa Al-Maraghi in Surah Al-Baqarah verses 142-143. Using qualitative methods with a literature study approach. Basically, wasatiah is a way of thinking that is not excessive, on the other hand making a good decision does not corner between two opposite sides. Ahmad Mustafa Al-Maraghi explained that the person who applies the wasatiah is the one who promotes justice with a neutral nature. The opposite of wasatiah is sufaha, that is, people who have minimal insight so as to cause extreme and radical thoughts. This study aims to gain an understanding of the meaning of wasatiah comprehensively, explaining verse by verse according to the topic of the verse discussed in the interpretation of Ahmad Mustafa Al-Maraghi in surah Al-Baqarah verses 142-143.